Blended and Hybrid Learning Models in Shaping PAI Students' Motivation : Model Pembelajaran Blended dan Hybrid Learning dalam Membentuk Motivasi Belajar Mahasiswa PAI - Ariansyah, Mochamad Yunus; Abid, Muhammad Fahri; Zaman, Badrus (Universitas Muhammadiyah Sidoarjo, 2024)
The World Health Organization (WHO) declared the Covid-19 or Corona outbreak in 2020, making it a global topic. To stop the spread of the coronavirus, several countries implemented lockdowns. Meanwhile, the Indonesian government decided to use physical distancing to stop the spread of Covid-19. However, this policy hampered growth in various fields. Education is one of the fields affected by Covid-19. In terms of education, it must be ensured that learning activities can be carried out successfully even though students are at home. The solution is that teachers must use social media or electronic-based media to create teaching and learning materials as an innovation. This is in line with the Decree of the Minister of Education and Culture contained in Circular Letter No. 04: 2020, which explains how policies will be implemented in the education sector amidst the spread of COVID-19. This research aims to determine the effect of hybrid and blended learning strategies on the learning motivation of students in the class of 2021 in the Islamic Religious Education study program at UIN Salatiga. This research uses a quantitative type of research. There are 2 classes in the sample, namely the experimental group which uses a hybrid learning model and the control group which uses a blended learning model. Using Google Forms, questionnaires were distributed for data collection purposes. Using the SPSS application, multiple linear regression analysis was used to analyze the data. Based on the results of this research, it can be concluded that student learning motivation is positively influenced by hybrid and blended learning models. Highlights: Blended vs. Hybrid Learning: Both models positively influence student motivation, but hybrid learning shows a stronger impact. Statistical Validation: Reliability and validity tests confirm the effectiveness of both learning models, with Cronbach’s alpha above 0.8. SPSS Analysis: Regression analysis indicates no heteroscedasticity issues, proving the models’ significance in improving learning motivation. Keywords: Blended Learning, Hybrid Learning, Motivation to Learn